ScanArray Core (1G 2012-2017) - Thybo, Hans; Balling, Niels; Maupin, Valerie; Ritter, Joachim; Tilmann, Frederik (The ScanArray consortium, 2012)
Abstract The ScanArray experiment is a major collaborative effort of institutions in Scandinavia and Germany to map crustal and mantle structure below Scandinavia using a dense temporary deployment of broadband seismometers. Scientific questions to be addressed include (among others): 1. What supports the topographic high of the Scandes? 2. How does lithospheric thickness vary within Fennoscandia? 3. What is the internal fabric of the mantle lithosphere? 4. Are there differences in the crustal structure between the different blocks of Fennoscandia? This data set, termed ScanArray core, comprises the temporary stations deployed by the University of Copenhagen, the University of Aarhus, and the University of Oslo, the Karlsruhe Institute of Technology (KIT) and the GeoForschungsZentrum Potsdam (GFZ) as part of the ScanArray experiment. Stations within this dataset are deployed for periods between 2 and 4 years. Data are available from the GFZ seismological data archive with network code 1G. Waveform data will be fully opened in early 2020. The wider ScanArray dataset additionally includes the multi-use temporary deployments Neonor2 (FDSN-code 2D, University of Bergen, NORSAR) and ScanLips3D (University of Leicester; archived at IRIS DMC), and the permanent networks of Sweden (UP, SNSN), Norway (NS, NNSN), Denmark (DK, DNSN) and Finland (HE, FNSN) as well as a subset of NORSAR stations (NO). The SNSN rearranged the distribution of broadband seismometers and deployed additional temporary stations to meet the objectives of the ScanArray experiment. ScanArray core and these other networks (except ScanLips3D) jointly form the virtual network _SCANARRAY. Partners of the ScanArray consortium are: University of Aarhus, Uppsala University, University of Oslo, University of Bergen, Karlsruhe Institute of Technology, NORSAR, University of Copenhagen, Deutsches GeoForschungsZentrum (GFZ) and Istanbul Technical University.